Effect of Water Quality on Operations of The Hospitality Industry in Kafue Catchment Area - Florence PHIRI; Selina BANDA; Jack KAALE; George KAMPAMBA; Margaret PANSHO (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2025)
Purpose: The study examined the effect of water quality operational costs of tourism establishments along the Kafue River in Zambia. It was conducted from middle Kafue River in Central province up to the confluents in Southern province. The objectives that guided the study were to; Ascertain perceptions of hospitality business owners on influence of water quality on operational costs in the catchment; Ascertain ways in which water was used in hospitality businesses located in the catchment; Determine measures used to sustain water quality cost operations in hospitality businesses in the catchment. Method: The study used a mixed methods approach and entailed application of a concurrent design. Data analysis entailed use of a quantitative-dominant mixed analysis which was supplemented by the qualitative one. A sample comprised of 60 respondents for the quantitative and 10 for qualitative. Data were collected simultaneously using a questionnaire and interview guide for quantitative and qualitative components respectively. Descriptive statistics were applicable in analyzing quantitative data using frequencies and percentages. Qualitatively, analysis of data was done using an inductive approach. Result: Business owners were skeptical about the quality of river water sources. The majority experienced positive effects of water quality on their business operations. The owners perceived effects of water quality on operational costs differently, which were both positive and negative. Not all the business owners used river water for drinking and bathing. Many of the business owners were aware and concerned about the quality of water they used in the hospitality establishments. Some owners experienced extra cost due to water quality while others did not. Extra costs were incurred due to water quality as experienced by a few owners, therefore, measures were put in place to operate their businesses. The majority of the owners put up measures to sustain their businesses. Contribution: This study which explored water quality and its effect on hospitality industry in the river catchment is important in revealing experiences which relate to operational costs. As a result, business owners can use the varied experiences as a basis for making informed decisions in improving water quality for the benefit of the industry. Ensuring good quality of water will become a shared responsibility not only for hospitality business owners, but also for other users in the catchment. Informing policy makers on how to come up with sustainable measures on the water quality supplied by the River. The study will also contribute to the existing body of knowledge on how to come up with sustainable measures on supplying quality water in hospitality industry.